Induction of reparative dentin by calcium silicate-based material as direct pulp capping agent (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This study was performed to examine whether calcium silicate could induce reparative dentin formation without eliciting any adverse effect in direct pulp capping of premolar teeth. Twenty participants who need extraction of their 4 healthy permanent premolar teeth for orthodontic reasons were included in this study. Following the surgical procedure, the exposed pulp tissue was treated either with calcium silicate or covered with calcium hydroxide paste. On day 3, 7, 14 and 28, the experimental teeth was extracted and examined using light microscopy and histometric analysis to observe the inflammatory changes and the amount of reparative dentin formation. The results showed that in the calcium silicate treated teeth, substantial amounts of dentine-like tissue was formed on day 14 and mostly located on the exposure site. It was also observed in the calcium hydroxide treated teeth but dentin-like tissue located at a distance from the exposure site. The total amount of reparative dentine formed in the calcium silicate-treated teeth was significantly higher (p